2017
DOI: 10.3390/ijerph14030267
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Earthquake Risk Information Seeking Behavior of the Victims: Evidence from Songyuan, China

Abstract: Efficient risk communication is a vital way to reduce the vulnerability of individuals when facing emergency risks, especially regarding earthquakes. Efficient risk communication aims at improving the supply of risk information and fulfilling the need for risk information by individuals. Therefore, an investigation into individual-level information seeking behavior within earthquake risk contexts is very important for improved earthquake risk communication. However, at present there are very few studies that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…After EFA was used to extract the dimensions, the results of the KMO test and Bartlett’s test of sphericity indicated that KMO almost exceeded 0.70 (see Table 2 ). This indicated that the set of data was suitable for the EFA [ 39 ]. All 28 items had a factor loading greater than 0.5, which corresponded to the six dimensions (see Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After EFA was used to extract the dimensions, the results of the KMO test and Bartlett’s test of sphericity indicated that KMO almost exceeded 0.70 (see Table 2 ). This indicated that the set of data was suitable for the EFA [ 39 ]. All 28 items had a factor loading greater than 0.5, which corresponded to the six dimensions (see Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Peers serve as main and confirmatory sources during bushfires; environmental cues, radio, and agency websites are also important [ 37 ]. For terrorist attacks [ 38 ], tsunami, and earthquakes [ 39 , 40 , 41 ], television and radio are the main sources. Overall, in disasters, public sources of disaster information, such as television and Internet news websites, are more trusted than private sources, such as one’s family, friends, and social networking connections.…”
Section: Theoretical Lens and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Zhang et al [ 34 ] recommend that when observers find someone performing unsafely, they should communicate with the worker in good faith, point out the unsafe behavior and suggest ways to work safely. Li et al [ 42 ] found that efficient risk communication is an important way to reduce the vulnerability of individuals when facing an emergency risk. Even Jiao et al [ 43 ] has used an interactive customized portal as a risk communication tool to enable residents to understand the potential risks of nearby industries.…”
Section: Methodsmentioning
confidence: 99%
“…Earthquakes are one of the most difficult hazards to be predicted and can result in massive casualties, property losses, and loss of municipal infrastructure. It is important for individuals to acquire sufficient earthquake disaster information so that, when faced with an earthquake, they are able to make the right decisions and take rapid actions with regard to mitigation measures and adjustments [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Research on the public’s disaster information acquisition content and channel preferences may help to improve the efficiency of information supply.…”
Section: Introductionmentioning
confidence: 99%